Talus fabric in Tuckerman Ravine, New Hampshire: Evidence for a tongue-shaped rock glacier - Thompson, David (Géographie physique et Quaternaire, 1999)
AbstractTuckerman Ravine is a glacial cirque located in the White Mountains of New Hampshire. The Ravine contains four talus accumulations formed through rockfall and toppling and characterized by large joint blocks with long axes of at least one meter. Previous research has classified one of the deposits (identified as Site 1 in the current study) variously as a moraine, a lobate rock glacier, and a protalus rampart. To resolve this controversy and provide a more reliable interpretation, block fabric analysis was performed at this and the other three talus sites. A bimodal fabric distribution was encountered at Site 1 and implies that the blocks at the base of the deposit collectively met some obstruction to movement. Such arrangement is not accounted for in simple talus accumulation models or in previous interpretations. The fabric data and its other characteristics support the classification of Site 1 as a relict tongue-shaped rock glacier. Fabric analysis indicates that the majority of blocks at Sites 2, 3, and 4 have a preferred orientation in the downslope direction and that these deposits represent rockfall talus which has not experienced post-depositional movement or activity. The mere presence of the talus deposits and their locations (which include the cirque headwall) do not support the reactivation of cirque glaciers in the White Mountains during the Holocene.